The Role of Husband Support in Work-Family Conflict Among Working Mothers (Perspective of Communal Sharing and Equity Matching) - Dewayani Soeharto, Triana Noor Edwina; Kuncoro, Mohammad Wahyu; Prahara, Sowanya Ardi (Gadjah Mada Journal of Psychology (GamaJoP), 2025)
This study aimed to determine the effect of the husband's support on work-family conflict in working mothers through the lens of equality matching and communal sharing based on the indigenous psychology approach. The data was collected from 296 participants through a survey using the work-family conflict scale, husband support scale, communal sharing social relationship scale, and social equality matching scale. Data analysis used was a test measurement model at once against 3 constructs using path analysis. Based on the results of the model test, it was found that the model of the influence of husband's support on work-family conflict in working mothers through social relations equality matching and communal sharing was empirically tested (kai-squared value with p> 0.05; GFI value ≥0.90; AGFI value. ≥0.90). In addition, it was found that the social relations of communal sharing have a direct influence on family work conflicts in working mothers with a total effect of -0.334 (p <0.05); Social relations equality matching has an effect on family work conflicts in working mothers with a total effect of -0.135 (p <0.05); and husband's support affects work-family conflict in working mothers with a total effect of -0.205 (p <0.05).